An Inductive Study of Feedback Interactions over the Course of Creative Projects - Harrison, Spencer H.; Rouse, Elizabeth D. (Academy of Management Journal, 2015)
While there is a large amount of literature on feedback, it is unclear how well traditional prescriptions for feedback apply during creative projects, since creativity often relies on nonlinear and ambiguous work patterns. We conducted an inductive study of feedback meetings in creative projects in two contexts—modern dance and product design—to understand how feedback might influence the development of creative prototypes. Our emergent findings reframe current theorizing on feedback by revealing its interactive nature: feedback providers and creative workers co-construct a problem space that provides openings for changing prototypes. Our analysis revealed sets of moves that feedback providers (personalizing, puzzling, measuring, and prescribing) and creative workers (backgrounding, forecasting, and opening) use to interact. We also found evidence that patterns among these moves helped guide one of two responses: (1) excavations, when feedback spurs comprehensive changes by prompting creative workers to return to old ideas, and (2) adjustments, when feedback spurs incremental refinements to the prototype. We integrate these findings into a process model that describes how feedback influences creative projects over time.